Virtual synchronous generators as potential solution for electricity Grid compliance studies - Murthy Balijepalli, V. S. K.; Ukil, Abhisek; Karthikeyan, N.; Gupta, Amit K.; Shicong, Yang (TENCON ... IEEE Region Ten Conference, 2016)
Concept of Virtual Synchronous Generator (VSG) to control inverters for emulating synchronous generator characteristics in grid integration of distributed energy resources (DER) is an emerging research area. Such distributed generators with diesel primeovers also have to comply to different electricity grid codes where Low Voltage Ride Through (LVRT) is a key requirement. VSG and LVRT are two independent topics, and has not been simultaneously studied. VSG approach to LVRT for grid compliance studies especially when connected in parallel to the diesel generators has not yet been explored. This has wider potential industrial applications in the paradigm of Smarter Grids. Considering the above, this paper presents the state-of-art literature review of the VSG and LVRT requirements in the changing grid (smart) environment. Further, analytical modeling of control of VSG for LVRT is presented for better understanding of the subject under discussion. Preliminary simulations established that the VSG as a potential solution for grid compliance studies. Finally, some future trends and challenges in the application of this technology in grid compliance studies, particularly as a solution for LVRT, are discussed to motivate future contributions.